The Existence of Customary Law in the Recognition and Protection of Collective Rights of Betawi Batik Motifs as Traditional Knowledge and Traditional Cultural Expressions (TCE) - Dhian Tyas Untari; Firman Maulana; Ahmad Syarif; Nyayu Maya Ardini; Muhammad Ali Mustofa; Hardjito S. Darmojo (International Journal of Education, Vocational and Social Science, 2026)
This study examines the existence and role of Customary Law in the recognition and protection of collective rights of Betawi Batik motifs as Traditional Cultural Expressions (TCE) and Traditional Knowledge (PK). Betawi Batik motifs have communal values ​​that are vulnerable to exploitation, and literature analysis shows that the formal Intellectual Property Rights (IPR) regime (Copyright and Industrial Design) is inadequate due to its individualistic nature and time constraints. This creates a protection gap against the collective rights of the Betawi community. This normative legal research uses a literature review, focusing on the synchronization of Customary Law norms and positive IPR. The results indicate that the principle of communal ownership and control functions through the Betawi Cultural Institution (LKB) still exist and are relevant. Therefore, this study constructs an integrative sui generis legal protection model. This model rests on three pillars: Communal Registration in the TCE database, Customary Control Mechanisms through BCIapproval, and Strengthening Ex-Officio Protection by the government. This model is expected to realize cultural justice and provide legal certainty for the preservation and commercialization of Betawi Batik in a sustainable manner. Keywords: Betawi Batik, Customary Law, Collective Rights, Traditional Cultural Expressions (TCE), Sui Generis Protection.